Antecedents of financial practice for the success of small and medium enterprises (SMEs) in Malaysia - Abdullah, Moha Asri; Azam, S. M. Ferdous (2018)
The purpose of this research is to assess the antecedents of financial practice for the success of Small and Medium Enterprises (SMEs) in Malaysia. The research method of this study is survey method, where the unit of analysis is the individual respondent consisting business owners and managers. A sample of 302 data is considered as the final sample size for the current study. Prior to conducting structural models, measurement models are performed to scrutinize the underlying dimensions of each and every construct. The reliability analysis is checked via Cronbach’s alpha coefficient of the four extracted factors for the purpose of ensuring the internal consistency. Finally, the hypothesis testing has been performed to achieve the purpose of this research. The results indicate that, although Financial Knowledge (FK) and Financial Behaviour (FB) are positively related to the Financial Practice (FP) in Malaysian SMEs, but these are not directly related to the Business Success (BS). Apart from this, the Financial Practice (FP) is found assertively allied to the Business Success (BS). Thus, Financial Practice (FP) plays the mediating roles as well in the Financial Knowledge (FK) toward Business Success (BS) in Malaysia. Therefore, this research conveys an understanding to the entrepreneurs regarding the financial knowledge items those are more essential and play as the remedy to get the business success swiftly. Furthermore, the current study creates the value in Malaysian SMEs since there is a dearth of empirical studies previously conducted highlighting the antecedents of financial practice for the success of Small and Medium Enterprises (SMEs) in Malaysia.